Multiple output differential OTA with linearizing bulk‐driven active‐error feedback loop for continuous‐time filter applications. (8th October 2014) - Szczepanski, Stanislaw; Pankiewicz, Bogdan; Koziel, Slawomir; Wojcikowski, Marek
Summary A CMOS circuit realization of a highly linear multiple‐output differential operational transconductance amplifier (OTA) has been proposed. The presented approach exploits a differential pair as an input stage with both the gate and the bulk terminals as signal ports. For the proposed OTA, improved linearity is obtained by means of the active‐error feedback loop operating at the bulk terminals of the input stage. SPICE simulations of the OTA show that, for 0.35 µm AMS process, total harmonic distortion at 1.36Vpp is less than 1% with dynamic range equal to 60.1 dB at power consumption of 276 μW from 3.3 V supply. As an example, both single output and dual differential OTAs are used to design third‐order elliptic low‐pass filters. The cut‐off frequency of the filters is 1 MHz. The power consumption of the OTA‐C filter utilizing the dual output differential OTA is reduced to 1.24 mW in comparison to 2.2 mW consumed by the single output differential OTA‐C filter counterpart. Copyright © 2014 John Wiley & Sons, Ltd.